2019
DOI: 10.3310/hsdr07170
|View full text |Cite
|
Sign up to set email alerts
|

A ‘telephone first’ approach to demand management in English general practice: a multimethod evaluation

Abstract: Background The increasing difficulty experienced by general practices in meeting patient demand is leading to new approaches being tried, including greater use of telephone consulting. Objectives To evaluate a ‘telephone first’ approach, in which all patients requesting a general practitioner (GP) appointment are asked to speak to a GP on the telephone first. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…Most published research on remote consultations is either marginal to general practice (for example, trials of video appointments for hospital outpatients with chronic stable conditions) 3 or lacking in granularity (for example, predominantly quantitative studies of telephone-first 'demand management'). 4 One detailed study of remote general practice consultations concluded that 'efficiency' gains, such as shorter consultations, may occur at the expense of other aspects of consultation quality, including information richness, shared decision making, and safety netting, 5 though another interpretation of this non-randomised study is that more patients with complex problems book face-to-face. A randomised trial of telephone triage in general practice found an overall reduction in efficiency because of double-handling of problems.…”
Section: Simplistic Policy; Sparse Evidencementioning
confidence: 93%
“…Most published research on remote consultations is either marginal to general practice (for example, trials of video appointments for hospital outpatients with chronic stable conditions) 3 or lacking in granularity (for example, predominantly quantitative studies of telephone-first 'demand management'). 4 One detailed study of remote general practice consultations concluded that 'efficiency' gains, such as shorter consultations, may occur at the expense of other aspects of consultation quality, including information richness, shared decision making, and safety netting, 5 though another interpretation of this non-randomised study is that more patients with complex problems book face-to-face. A randomised trial of telephone triage in general practice found an overall reduction in efficiency because of double-handling of problems.…”
Section: Simplistic Policy; Sparse Evidencementioning
confidence: 93%
“…Previous research on telephone consultations is surprisingly sparse and supports no firm conclusions, though several studies have suggested that double-handling may reduce efficiency (32,(98)(99)(100)(101)(102). There was very little research on e-consultations prior to the pandemic, and findings were limited (12,(103)(104)(105)(106)(107).…”
Section: Comparison With Previous Researchmentioning
confidence: 99%
“…Early evaluations of telephone triage approaches found that their introduction meant that patients saw or spoke to a clinician more quickly, but that the number of patient contacts increased overall, with no evidence of a reduced GP workload or of cost savings. [18][19][20][21][22] These evaluations also found evidence of strong variation between general practices in the impact of introducing telephone triage on patients' experience of their practice and on changes in secondary care use. There was also variation in how well practices adapted to the approach, with a substantial minority of practices reverting to nontelephone triage approaches after trialling the innovation.…”
Section: Introductionmentioning
confidence: 88%